Theoretical study on narrow Fano resonance of nanocrescent for the label-free detection of single molecules and single nanoparticles. Issue 7 (19th January 2018) - Zheng, Chunjie; Jia, Tianqing; Zhao, Hua; Xia, Yingjie; Zhang, Shian; Feng, Donghai; Sun, Zhenrong
Abstract : The narrow Fano resonance caused by the strong narrow resonant absorption is highly sensitive to a trapped nanoparticle. Abstract : This paper reports a narrow Fano resonance of 3D nanocrescent and its application in the label-free detection of single molecules. The Fano resonance depends not only on the gap size but also on the height. The Fano resonance originates from the interference between the quadrupolar mode supported by the horizontal crescent and the dipolar mode along the nanotip. When the height of 3D nanocrescent is 30 nm, the width of Fano resonance is as narrow as 10 nm. The narrow linewidth is caused by the strong narrow resonant absorption coming from the dipolar mode of nanotip overlapping with the quadrupolar mode of nanocrescent, where the absorption spectra are calculated under a horizontal incident light. The narrow Fano resonance is highly sensitive to a single nanoparticle trapped by the nanocrescent. The wavelength shift increases linearly with the refractive index with the relation of Δ λ = 22.10 n − 28.80, and increases with the size of trapped nanoparticle following a relation of Δ λ = 0.826 × r 1.672 . These results indicate that if a protein nanoparticle with radius of 2.5 nm is trapped by the nanocrescent, the shift is as large as 4.03 nm.